Rancang Bangun Aplikasi Panggil Tukang Berbasis Android di Daerah Surabaya - Nadia Felicia Wianda; Agustinus Noertjahyana; Lily Puspa Dewi (Jurnal Infra, 2022)
Nowadays, many people are using android applications in their daily lives. Many kind of applications have been made to make everyday jobs and daily routines become simpler and easier. Looking for AC Service and home repairman is one of them. In Surabaya, looking for service providers is stil use with manual search which is asking to their neighboor. But the problem is, when the people just move in the new neighborhood, and just barely know anyone around, or urgently need to repair your air conditioner problem, and they just don't know whom to ask for help. Because of the problem, Writer make an application Panggil Tukang for helping people find good technicians especially people who lives in Surabaya. The features available on this application will be help the user to find the right technician. The user can get the interesting experience to find a good technicians in this application. Features such as price negotiation, payment methods, and chat will help the user to communicate with the service provider to find the best solution for them. This application simply make life much easier for people who are looking for the right technician's help. On the other hand, this application also provide help for all the technicians' service provider who are looking for people who needs their service. The application and website were built base on PHP language code and Kotlin. While the database we are using to make this application is Firebase.